Konteks Sosiocultural Practice pada Lagu “Oras Loron Malirin” (Analisis Wacana Kritis Norman Fairclough) - Rozario Mendonca Da Costa (Sekolah Tinggi Ilmu Administrasi Yappi Makassar, 2023)
This research is entitled The context of sociocultural practice in the song